Impacts of double rotating cylinders on the forced convection of hybrid nanofluid in a bifurcating channel with partly porous layers. (August 2021) - Kolsi, Lioua; Selimefendigil, Fatih; Öztop, Hakan F.; Hassen, Walid; Aich, Walid
Abstract: Impacts of using double rotating cylinders and partly porous layers in the bifurcating channels on the hydro-thermal performance were numerically assessed. Hybrid nanoparticles were used in water and finite element method was selected as the solver. Effects of Reynolds number, rotational speeds of the cylinders and their locations in the bifurcating channels, porous layer sizes and nanoparticle solid volume fractions on the hydro-thermal performance features were explored. The contribution of different hot wall parts was changed with varying Reynolds number and rotational velocity of the cylinders. Depending upon the rotational direction of the cylinders, the vortex occurrence and size at the bifurcations change significantly. Heat transfer considering all hot walls rise with higher rotational speeds in both directions. The amount of improvement in the heat transfer rate becomes 25 % and 19 % with varying speeds of the cylinders as compared to motionless cylinders. The pressure coefficient reduces with increasing the second cylinder speed in clockwise direction and this is favorable for thermal performance since the heat transfer also increases. The overall impact of the varying horizontal locations of the cylinders on the heat transfer rate is slight. The separated zones at the branching depends on the porous layer sizes. The overall heat transfer behavior becomes opposite when varying the sizes of the porous layers in the horizontal and vertical channels. By using nanoparticles in the base fluid, 35.75 % improvement in the heat transfer rate is achieved for vertical wall at Re = 350 while pressure drop coefficient rises by about 8.5 % . The overall improvement in the heat transfer rate by using nanofluid is 26 % . Owing to diverse use of bifurcating channels in thermal engineering from fuel cells to electronic cooling, the proposed methods of heat transfer enhancement techniques can be considered simultaneously for effective control the thermal performance of those systems.